Third Place Design Strategy for Commuter in Sub-urban (Case Study: Outdoor Public Space in Tangerang City, Indonesia) - Mustika Kusumaning Wardhani; Tomohiko Yoshida; Alpraditia Malik (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2020)
In recent years, Urban population density spreads towards suburbs of the metropolitan city as the impact of urbanisation. In Indonesia, Commuting activity does not only occur in the centre of metropolitan city Jakarta but spreads outside to the suburbs such as in Tangerang City. Commuting activities often cause stress, and some outdoor public spaces are expected to be healing space for recreation needs amidst a busy life. The lack of integration of urban design that supports commuting activities along with leisure activities is a problem that will be raised. This paper aims to evaluate the configuration of a potential location as the third space in Tangerang City infrastructure around bus stops and train station. Methods used are qualitative methods with a rationalistic approach. The research findings postulated three paradigms in Tactical Urbanism design strategy, which are: (1) Functionally, Tactical Urbanism can form a multipurpose proximity network that functions simultaneously between mobility and relaxation activities; (2) Socially, tactical urbanism design strategy can eliminate social segregation where there are no gaps to spend leisure time around Tangerang station for commuter, community, also tourist; (3) Visually, Tactical Urbanism can encourage people to come and sit for a while and become an icon of Tangerang City with the design of public open spaces integrated with infrastructure for transportation. Based on the above findings, a framework is conceptualised as an attempt to strengthen the tactical urbanism design strategy in the suburbs area.